Análise termodinâmica e ambiental do aproveitamento energético do biogás do aterro sanitário metropolitano de João Pessoa - Bispo Junior, Djayr Alves (2022)
The concern about the amount of Urban Solid Waste (MSW) is an increasingly present problem in modern society. This is a consequence of rapid population growth, which causes the amount of MSW to grow over the years. There are some examples of treatments that can be used for organics, such as an energy and environmental solution, biogas. This renewable source can be treated through the decomposition of organic particles, through biochemical digestion and biomass in a process. This procedure takes place in sanitary landfills. the present work focuses on the use of biogas from the Metropolitan Landfill of João Pessoa, Paraíba. A systematic review was carried out on the various ways of using biogas on a global scale. The Life Cycle Assessment (LCA) methodology was applied to quantify the environmental impacts of materials and their respective means of transport until arrival in the city. A thermodynamic analysis was also carried out for a possible implementation of a Rankine cycle to the landfill biogas plant. The dimension report on technical visits, consultation data from the authors' manuals, and scientific literature review were published in the proposed system. Software Engineering Equation Solver (EES) was used for thermodynamic calculations. The work shows a vast possibility of using biogas, through the 17 articles identified in the systematic review, highlights the importance of recycling, an environmental benefit of around 25% compared to greenhouse gases and concludes that the best cycle for integration into the studied landfill biogas plant is the Rankine cycle with reheating, with better energy efficiency and greater electrical energy productivity in the process.